2010
DOI: 10.1128/aac.01347-09
|View full text |Cite
|
Sign up to set email alerts
|

Pradimicin S, a Highly Soluble Nonpeptidic Small-Size Carbohydrate-Binding Antibiotic, Is an Anti-HIV Drug Lead for both Microbicidal and Systemic Use

Abstract: Pradimicin S (PRM-S) is a highly water-soluble, negatively charged derivative of the antibiotic pradimicin A (PRM-A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 30 publications
1
52
0
Order By: Relevance
“…Seven of the above-mentioned glycosylation sites were high-mannosetype N-glycans, and only five mutations reflected a complextype N-glycan deletion. Such predominant selectivity for the deletion of high-mannose-type glycans under AH pressure has also been observed for the cyanobacterial lectin CV-N (2, 43, 48) and the ␣1,2-mannose-specific antibiotics pradimicin A and S (4,7). This points to the pronounced preference of AH to bind to high-mannose-type glycans.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Seven of the above-mentioned glycosylation sites were high-mannosetype N-glycans, and only five mutations reflected a complextype N-glycan deletion. Such predominant selectivity for the deletion of high-mannose-type glycans under AH pressure has also been observed for the cyanobacterial lectin CV-N (2, 43, 48) and the ␣1,2-mannose-specific antibiotics pradimicin A and S (4,7). This points to the pronounced preference of AH to bind to high-mannose-type glycans.…”
Section: Discussionmentioning
confidence: 64%
“…A variety of carbohydrate-binding agents (CBAs), such as the prokaryotic agent cyanovirin-N (CV-N) (7)(8)(9)(10), the plant lectins Hippeastrum hybrid agglutinin (HHA) (1) and Galanthus nivalis agglutinin (GNA) (1), and the antibiotics pradimicin A and S (PRM-A and PRM-S, respectively) (4, 7), have been described to inhibit viral entry, presumably by their interaction with the glycans on HIV gp120. It has indeed been demonstrated that CBAs block virus entry by inhibiting the fusion of cell-free HIV virions with their target cells.…”
mentioning
confidence: 99%
“…The fact that the glycans on Asn 339 and Asn 386 of the MVN-res virus were only partially deleted can explain why the virus showed some cross-resistance to CV-N (4-fold resistance). The ␣(1,2)-mannose-specific PRM-S appeared to be 5-fold less active against MVN-res virus, and it is reported that a PRM-S-resistant IIIB virus has, among other mutations, also a mutation deleting the glycan on Asn 295 (39). Thus, it seems that Asn 295 might be an important glycan for the activity of PRM-S, and this can explain its reduced activity against the MVN-res virus.…”
Section: Discussionmentioning
confidence: 99%
“…To date, twelve additional members of PRM with antimicrobial activity have been identified ( In addition to scientific interest in their Man binding property, medicinal significance of PRMs is also rapidly growing since Balzarini and coworkers proposed that PRMs are promising leads for conceptually novel drugs for human immunodeficiency virus (HIV) with a dual mechanism of antiviral action (36). PRM-A and PRM-S have been found to block the virus entry to the host cells and force the virus to progressively delete the envelope glycans that shield against the host immune system (37,38). These antiviral effects are ascribed to its specific binding to the high-mannose-type glycans on the viral envelope.…”
Section: Naturally-occurring Cbmsmentioning
confidence: 99%